(3NWH eMeO Hf fHGJIs - (3CHhWGgQ eMeO Hf YHO GdQMje Hf eMeO Hf ESeGYjd Hf fHGJIs; (3eMeO Hf CHj jMji YHO GdQMje Hf eMeO Hf ESeGYjd Hf fHGJg,J (B762 (3g` s
(3ChdgG (B:s
(3NWHI CNQi aj PcQ GdLgGO hMaQ GdNfOb Mhd ShQeqjG aGQbjf hPdc jhe GdLeYI dYTQ Ndhf ef UaQ, hef BPGQ ef SfI GKfJjf hNeSjf hKdGK eGFI s
(3BNQgG (B:s
(3aUd BNQ NWHI aj eOM GdNdaGA hGdUMGHI s
(3hGfXQ NWHg CjVkG eY NWH YHOGdQMje Hf fHGJI hGdOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B286 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs